MENINGKATKAN KOMPETENSI UMKM SANIE COOKIES MELALUI PELATIHAN PENYUSUNAN LAPORAN KEUANGAN LABA RUGI BERBASIS MICROSOFT EXCEL - Malelak, Mariana Ing; Prayogo, Nathania Cherryl; Purnomo, Celine Natasha; Sofian, Merviona; Hartanto, Delon (Universitas Mataram, 2024)
Micro, Small, and Medium Enterprises (MSMEs) have been recognized by Bank Indonesia as one of the important pillars in the Indonesian economy. This is because MSMEs make a significant contribution to Gross Domestic Product (GDP), employment, and serve as a support for the stability of the country's economy. However, in reality, the growth number of MSMEs in Indonesia is not always accompanied by an increase in their sales. One of the reasons is the lack of awareness among entrepreneurs about the importance of keeping financial records such as profit and loss statements. Therefore, the purpose of this community service activity is to enhance the competency of MSMEs, particularly Sanie Cookies, through training in financial report preparation using Microsoft Excel application. The activity method is divided into 3 stages: preparation, implementation, and evaluation. The preparation stage includes selecting partners and group discussions. Implementation is carried out in the form of guidance and assistance in preparing profit and loss financial statements. Evaluation is conducted by considering feedback and suggestions from partners. The results of the activity show that after identifying the challenges faced by Sanie Cookies, there are 5 topics that are suitable and relevant for the company: accounting fundamentals, the importance of separating personal and business finances, methods of preparing financial statements, using Microsoft Excel as a tool for managing financial data, and operational cost analysis. During the meetings, there was two-way communication so that the material given could be understood and absorbed by Sanie Cookies. The activities successfully achieved their goals, as reflected in the seriousness of Sanie Cookies in learning and understanding, and their ability to apply accounting concepts according to the company's reality. Knowledge transfer in the form of training and mentoring helped enhance Sanie Cookies' competency in preparing financial reports using Microsoft Excel.